Increasing Interest in Early Childhood Learning in North Tapanuli through the Implementation of the Adiwiyata School Concept - Endang Junita Sinaga; Hisardo Sitorus; Ledyana Dwi Mei Situngkir; Winarti Agustina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
In learning, interest from every child is needed so that they can absorb and understand every material presented by the teacher. However, in reality, children's interest in learning is often erratic, so their concentration is not focused. The purpose of this study was to determine the implementation of the Adiwiyata school concept for early childhood to increase the learning interests in 10 kindergartens throughout North Tapanuli Regency, with similar problems. The implementation of Adiwiyata was predicted incresing interest of early childhood in learning. This research was conducted in all kindergarten schools in North Tapanuli Regency which was carried out from April to October 2022 and used a mixed method approach, which is a mixture of qualitative and quantitative. Based on research that has been carried out in the field, the implementation of the adiwiyata school concept in North Tapanuli Regency Kindergarten is relatively good. This is based on the average value (mean) of the implementation of the adiwiyata school concept in the high category. Meanwhile, all students have a high interest in learning. Through this research, it is hoped that ECCE educators and education staff will make new innovations in the environment so that they can get the concept of adiwiyata to be achieved optimally